Transient thermal circuit model optimization for power cables with axial heat dissipation - Qin, Tonghui; Ma, Aiqing; Su, Huangxiang; Cao, Xinao (Frontiers in Energy Research, 2025)
As a critical component for power transmission in electromagnetic systems, power cables generate operational losses that induce coupled electromagnetic-thermal effects. Traditional thermal circuit models for power cables typically assume uniform external heat dissipation conditions and focus on the temperature variation at a cross-section to represent the thermal state of the entire cable. However, in practical applications where environmental conditions vary or multiple heat sources exist, axial heat exchange within the cable leads to temperature differences along its length, rendering conventional models inadequate. To address this limitation, this study proposes a full-length transient thermal circuit model for power cables that incorporates axial heat dissipation. The model achieves multiphysics coupling in power cables by converting electromagnetic losses into thermal sources. Based on heat transfer principles, it accounts for the thermal interactions between the cable body, surrounding soil, and external heat sources. A 110 kV underground power cable is used as a case study, with the model leveraging the analogy between electrical and thermal networks to calculate temperature rise along the cable. The model’s predictions are validated against experimental data, finite element simulations, and traditional thermal circuit results, confirming the accuracy and effectiveness of the model. Unlike traditional models that assume uniform external heat dissipation conditions, the proposed model incorporates axial heat dissipation mechanisms to achieve precise prediction of axial temperature gradients in heterogeneous environments, providing a practical and computationally efficient solution for real-time temperature monitoring and intelligent maintenance of power cables in power system under complex and variable environments.